The effects of monetary rewards on volunteers' effort - experimental evidence in Singapore. - Liow, Jia Min. (2013)
In a situation with a Principal-Agent problem, the principal will design a remuneration to induce optimal work effort. Fundraising is a typical principal-agent problem where charitable organization is unable to observe the work effort of volunteers. Our study aims to find out the effects of monetary incentives on the work effort of volunteers and other factors which contribute to the differences in the work effort, in Singapore context. As such, we conducted a field test during the Glory Centre Community Services Association 2013 Flag Day. Our results showed that intrinsic motivations due to warm glow and volunteer’s personality (extraversion) play important roles in determining work effort. In addition, monetary incentives have a detrimental effect on work effort and should not be used in a fundraising event.